2014
DOI: 10.4103/2303-9027.123007
|View full text |Cite
|
Sign up to set email alerts
|

When to puncture, when not to puncture: Pancreatic masses

Abstract: Endoscopic ultrasound (EUS) has evolved to become a crucial tool for the evaluation of pancreatic diseases, among them solid pancreatic lesions. However, its ability to determine whether a lesion is malignant or not is difficult to establish based only in the endosonographic image. EUS-guided fine needle aspiration (EUS-FNA) allows obtaining a cytological and/or histological sample from pancreatic lesions, with a high overall accuracy and low complication rates. Although the clinical usefulness of EUS-FNA for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 80 publications
1
10
0
Order By: Relevance
“…1 In a recent prospective study of adverse events of EUS-FNA, puncture of https://doi.org/10.15279/kpba.2018.23. 4.165 cystic lesions was similarly complicated in solid masses compared with previous studies. 2 Severe hemorrhage associated with the procedure was rarely reported.…”
Section: Introductionsupporting
confidence: 50%
See 2 more Smart Citations
“…1 In a recent prospective study of adverse events of EUS-FNA, puncture of https://doi.org/10.15279/kpba.2018.23. 4.165 cystic lesions was similarly complicated in solid masses compared with previous studies. 2 Severe hemorrhage associated with the procedure was rarely reported.…”
Section: Introductionsupporting
confidence: 50%
“…However, recent studies reported that the complication rate for cystic lesions was comparable to that of solid lesions and the rate of severe complications such as perforation, infection or hemorrhage is extremely rare and the overall mortality rate was near 0.2%. 2,4,8 Periprocedural planning based on a comprehensive review of the clinical records and imaging studies can minimize the complications. lines have yet to be established.…”
Section: Casementioning
confidence: 99%
See 1 more Smart Citation
“…In the elderly, the identification of pancreatic masses is usually considered sufficient for the diagnosis of pancreatic cancer and therefore only palliative and supportive care is prescribed. According to several guidelines [ 1 , 2 ], fine needle ago-biopsy is recommended only for patients with unresectable lesions to confirm the diagnosis and aid in decision-making regarding chemotherapy and radiation therapy. Therefore, in aged patients the risk-benefit assessment of this procedure and the lack of chemotherapy indications generally preclude any invasive biopsies.…”
Section: Introductionmentioning
confidence: 99%
“…A histological grading of pancreatic inflammation and fibrosis has the additional potential benefit of being used as an endpoint in future therapeutic trials. The implementation of tissue acquisition via EUS in solid pancreatic lesions has had a major impact on the diagnosis and subsequent management of pancreatic cancer (8)(9)(10)(11)(12). Moreover, EUS-guided fine needle aspiration (FNA) or biopsy (FNB) is safe and reliable (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%